Tryptophan Metabolism in Digestive and Extra-Digestive Diseases: Mechanisms, Clinical Implications, and Therapeutic Perspectives - Ege Tohumcu; Francesca Sofia Puca; Varol Tunali; Lucia Cerrito; Maria Pallozzi; Leonardo Stella; Marta Maestri; Celeste Ambra Murace; Serena Porcari; Simone Varca; Andrea Severino; Antonio Gasbarrini; et al. (Nutrients, 2026)
Tryptophan (Trp) metabolism lies at the intersection of nutrition, gut microbiota, mucosal immunology, and systemic inflammation—processes that play key roles in many gastrointestinal and extraintestinal diseases. Trp is an essential amino acid obtained through dietary intake. Beyond its role in protein synthesis, it is metabolized through three principal pathways: the kynurenine pathway, the serotonin/melatonin pathway, and microbial metabolism in the gut leading to indole and related derivatives. The kynurenine pathway represents the primary route of Trp degradation and is strongly linked to inflammatory signaling. The serotonin pathway is particularly important for gastrointestinal physiology, influencing motility, secretion, and visceral sensitivity. In parallel, microbial Trp metabolism produces metabolites that regulate epithelial barrier integrity, modulate mucosal immune responses, and contribute to communication along the gut–organ axes. Across different disease states, several recurring patterns emerge. Inflammatory conditions frequently shift Trp metabolism toward the kynurenine pathway through increased IDO1 or TDO activity, resulting in changes in kynurenine metabolites and in the kynurenine-to-tryptophan (Kyn/Trp) ratio. At the same time, reduced microbial production of indole derivatives may impair aryl hydrocarbon receptor signaling and weaken barrier-protective and immunoregulatory mechanisms. Alterations in the serotonin pathway are also associated with disturbances in gastrointestinal motility and gut–brain communication. Together, these observations highlight Trp metabolism as an important framework for understanding interactions between diet, microbiota, and host responses in health and disease. However, it is important to clarify that much of the currently available evidence remains associative or is derived primarily from preclinical models. This narrative review, based on literature retrieved from major biomedical databases (e.g., PubMed/MEDLINE, Scopus, and Web of Science), aims to provide an updated synthesis of current knowledge on Trp metabolism in disease pathophysiology. Furthermore, while we highlight potential translational applications—such as proposed biomarker development and targeted therapeutic strategies—these perspectives have been moderated to acknowledge the limited level of clinical validation established to date.